Upaya Sekolah dalam Membangun Literasi Diigtal Siswa di SMK Negeri 1 Tuban - Astutik, Rika; Harmanto (Universitas Negeri Surabaya (Unesa), 2025)
This research aims to describe the school's efforts to build students' digital literacy at SMK Negeri 1 Tuban. This type of research is qualitative. With a case study design The research informants were the school principal, Waka, digital library coordinator, public relations, teachers, students. Data collection techniques use observation, interviews, documentation. Data analysis technique using the Miles and Huberman model. The research results show that the school's efforts to build students' digital literacy at SMK Negeri 1 Tuban were carried out through outreach and workshops related to digital literacy, creating a digital library, tests using CBT, learning to use IT/technology. In the school's efforts to build students' digital literacy in terms of the four pillars of digital literacy, the school has implemented the four pillars of digital literacy which include proficiency, safety, ethics and digital culture. The implementation of these four pillars was carried out intentionally and unintentionally. Supporting factors for the school's efforts to build students' digital literacy include support from the school principal, adequate facilities and infrastructure, clear bureaucratic flow, and students who are competent in using technology. Factors inhibiting schools from developing students' digital literacy include hacker interference, students' lack of awareness of GLS, not all best-selling books are available in digital libraries, the school's LMS is suspended, teachers prefer to use technology-based learning which is easy and optional.